Prevalencia de caries de infancia temprana y su relación con los factores de riesgo asociados en preescolares de 3 a 5 años en el distrito de Cajamarca, 2016 - Uribe Uribe de Barrenechea, Yenny Oriele (2017)
ABSTRACT Objective: The purpose of this study was to determine the prevalence of early childhood caries and its relation with the associated risk factors in preschool children aged 3 to 5 years in the district of Cajamarca, 2016. Materials and methods: Prospective cross-sectional, descriptive, and correlational study where a sample of 149 3 to 5-year-old preschoolers of both genders met the inclusion and exclusion criteria. Results: The Prevalence of Caries of Childhood was 78.5%, the masculine gender and the age of 4 years, were the most affected. The mean salivary flow was 0.37 ml / min, and salivary pH 6.56. Among the risk factors that altered the presence of early childhood caries, parental occupation had a higher significance, with a value of OR = 3.54. Conclusions: It is concluded that 78.5% of preschoolers aged 3 to 5 years of the district of Cajamarca present early childhood caries, with a significant relationship with parental occupation as a risk factor.